Ovarian Dynamic in Ongole Grade Cattle after GnRH Injection in Ovsynch Protocol Based on Progesterone Device - Muhammad Imron; Iman Supriatna; . Amrozi; Muhammad Agus Setiadi (Faculty of Animal Science, Bogor Agricultural University, 2015)
PO cattle have weaknesses to show clear estrus signs which cause difficulty in artificial insemination implementation. The present study was designed to obtain ovarian dynamic as effect of GnRH injection in ovsynch protocol based on progesterone intravaginal device. Heifers (18) and cows (n= 12) were allocated to one of three groups. Cuemate-PGF2α (CP) group inserted with a Cuemate on day 0-7 and injected with prostaglandin on day 7. Cuemate-PGF2α-GnRH (CPG) group was treated as CP group with the addition of GnRH injection on day 9. GnRH-Cuemate-PGF2α-GnRH (GCPG) group was treated as CPG group with addition of GnRH injection on day 0. Ultrasonography was performed on days 0-3, day 7 until ovulation and 7 days after ovulation. Percentage of ovulation synchronization increased significantly (P<0.01) between CP, CPG, and GCPG, respectively, both in heifers (16%, 50%, and 85%, respectively) and cows (0%, 60%, and 100%, respectively), on day 11. Preovulatory follicle diameters between CP, CPG, and GCPG treatments were not different significantly both in heifers (11.9±0.5, 11.9±0.5, and 12.1±0.6 mm, respectively) and cows (11.7±0.4, 11.8±0.7, and 11.1±0.6 mm, respectively). This study concluded that GCPG protocol increased the synchrony of ovulation rate both in cows and heifers, without affecting the follicle preovulatory and CL diameters.Key words: ovarian dynamic, GnRH, ovsych, PO Cattle